2016
DOI: 10.1093/tropej/fmv100
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations of Hyponatremia and Hypernatremia in Under-Five Diarrheal Children in a Diarrhea Hospital

Abstract: Early diagnosis and prompt management of hypo- and hypernatremia by identifying simple clinical predicting factors of these two conditions in diarrheal children <5 years of age is critically important to prevent deaths in such children, especially in resource-limited settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 24 publications
7
43
2
4
Order By: Relevance
“…However, a number of previous studies reported strong association of death with severe malnutrition, 9-11 hypoxemia, 3,12 hyponatremia, 13,14 and female sex. 14,15 …”
Section: Discussionmentioning
confidence: 93%
“…However, a number of previous studies reported strong association of death with severe malnutrition, 9-11 hypoxemia, 3,12 hyponatremia, 13,14 and female sex. 14,15 …”
Section: Discussionmentioning
confidence: 93%
“…Die wesentliche Komplikation einer hyponatriämischen Dehydration ist die Entwicklung einer hyponatriämischen Enzephalopathie mit Hirnödem, erhöhtem Hirndruck, gestörter Perfusion und selten auch Hirnstammeinklemmung [86,133]. Aufgrund der Verwendung von hypotonen intravenösen Rehydrationslösungen kann es auch iatrogen während der Behandlung zur Hyponatriämie kommen [134] (siehe II.2.8).…”
Section: Ii21 Empfehlungunclassified
“…Bei einer AGE wird bereits aufgrund des Volumendefizits und Erbrechens vermehrt antidiuretisches Hormon (ADH) gebildet, sodass hypotone Lösungen bei AGE nicht geeignet sind und zur Prävention der Hyponatriämie 0,9 %ige NaCl-Lösung verwendet werden soll [133,135]. Die klinischen Symptome können unspezifisch sein und mit Übelkeit und Erbrechen nicht von den üblichen Symptomen der AGE unterscheidbar sein, aber bis hin zu Bewusstseinsstörungen und Krampfanfällen reichen [86]. In seltenen Fällen können Herzrhythmusstörungen oder auch ein neurogenes Lungenödem auftreten.…”
Section: Ii21 Empfehlungunclassified
“…One author notes, "physicians who are anxious about a patient's problem may be tempted to do something-anything-decisive in order to diminish their own anxiety." 5 Severe electrolyte derangements are common in developing countries 6 but less so in the United States. A prospective pediatric dehydration study over 1 year in the United States demonstrated rates of 6% and 3% of hypo-and hypernatremia, respectively (n = 182).…”
Section: Why Physicians Might Think Electrolyte Testing Is Helpfulmentioning
confidence: 99%